The Correlation of Students’ Habit in Listening a Song and Mastering a Vocabulary: English - Sirrul Bari; Innani; Musdalifah Musdalifah; Annisa Kurnia Asri (JOEY: Journal of English Ibrahimy, 2024)
The study was aimed for finding out whether there was a significant correlation between students' habit in listening a song and students’ mastering a vocabulary or not. The research was conducted at the first grade in SMP 11 Ma'arif Bangsalsari Jember. This research useda correlation method, and there were two research variables, students’ habit in listening a song as variable X and students’ mastering a vocabulary as variable Y. The researcher useda random sampling technique. In this research, the researcher gave a test to the students. The result of test showed that the level correlation between a students’ habit in listening a song and mastering a vocabulary was high with sig 0,000 and r count 0,696. It showed that there was a significant correlation between students’ habit in listening a song and students’ mastering a vocabulary.